2020
DOI: 10.3389/fpsyg.2020.575024
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the Impostor “Syndrome”

Abstract: The impostor “syndrome” refers to the notion that some individuals feel as if they ended up in esteemed roles and positions not because of their competencies, but because of some oversight or stroke of luck. Such individuals therefore feel like frauds or “impostors.” Despite the fact that impostor feelings are often linked to marginalized groups in society, to date, research predominantly approaches this phenomenon as an issue of the individual: pointing toward individuals for the roots and solutions of the “s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 59 publications
2
83
0
3
Order By: Relevance
“…Combined with the gender differences in science identity discrepancy, we posit that while female students within our class may feel less capable than those around them, a quantified self-assessment of their own ability suggests otherwise. These gender differences are not necessarily surprising since females in several fields indicate greater imposter syndrome than males (25,26). However, it reinforces the importance of still pursuing systemic improvements that encourage women in STEM regardless that the National Institutes of Health no longer considers women as underrepresented in the biomedical sciences.…”
Section: Discussionmentioning
confidence: 90%
“…Combined with the gender differences in science identity discrepancy, we posit that while female students within our class may feel less capable than those around them, a quantified self-assessment of their own ability suggests otherwise. These gender differences are not necessarily surprising since females in several fields indicate greater imposter syndrome than males (25,26). However, it reinforces the importance of still pursuing systemic improvements that encourage women in STEM regardless that the National Institutes of Health no longer considers women as underrepresented in the biomedical sciences.…”
Section: Discussionmentioning
confidence: 90%
“…Combined with the gender differences in science identity discrepancy, we posit that while female students within our class may feel less skilled than those around them, a quantified self-assessment of their own ability suggests otherwise. These gender differences are not necessarily surprising, since females in several fields indicate greater imposter syndrome than males ( 25 , 26 ). However, it reinforces the importance of still pursuing systemic improvements that encourage women in STEM regardless that the National Institutes of Health no longer consider women underrepresented in the biomedical sciences.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, only male imposters were significantly affected by negative feedback and conditions with high accountability, probably affecting their competence-based self-views and their self-esteem. That is, context factors that may drive differences between women and men should be taken into account in future studies to better understand the inconsistently observed gender differences in the IP (for a detailed discussion on the importance of contextual factors in understanding the IP, see Feenstra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%